Stock market predictability 2000–2014: The effect of the great recession - Michail, Nektarios A. (My University, 2019)
The return predictability of 242 companies with continuous daily trading in the Standard and Poor’s index during the 2000–2014 period is examined using rolling variance ratio tests. The results indicate that predictability is time-varying and stock-specific, a finding which is in accordance to the adaptive market hypothesis. During the great recession the number of stocks whose returns were found to be predictable increased substantially, especially during the period of Lehman Brothers bankruptcy. Importantly, predictability is found to be driven by changing market conditions, such as stock market volatility and economic fundamentals.
Keywords: Adaptive markets; Great recession; Mean reversion; Stock market predictability